2006
DOI: 10.1637/7514-020706r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cytolethal Distending Toxin of Campylobacter jejuni on Adhesion and Internalization in Cultured Cells and in Colonization of the Chicken Gut

Abstract: Campylobacter jejuni produces cytolethal distending toxin (CDT) that causes host cells to arrest during their cell cycle and that is involved in the pathogenesis of inflammatory diarrhea in humans. To assess the role of CDT in adherence and invasion of different cultured host cells (HeLa and HD-11) and in colonization of the chicken intestine, the genes of C jejuni NCTC11168 encoding the toxin subunits (cdtA, cdtB, and cdtC) were inactivated by insertional mutagenesis. No significant difference was found in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…This cytotoxin arrests eukaryotic cells to the G2 phase of the cell cycle, preventing them from entering mitosis, and leading to cell death. The toxin was named according to the morphological changes associated with its cytoplasmic distension action and its function is well documented 8,43 . In the present study, 74.3% of the C. jejuni strains carried the cdt complex.…”
Section: Discussionmentioning
confidence: 99%
“…This cytotoxin arrests eukaryotic cells to the G2 phase of the cell cycle, preventing them from entering mitosis, and leading to cell death. The toxin was named according to the morphological changes associated with its cytoplasmic distension action and its function is well documented 8,43 . In the present study, 74.3% of the C. jejuni strains carried the cdt complex.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to having a cytotoxic effect, it has been suggested that cdt may play a role in adherence and invasion of bacteria to the host cells (Biswas et al, 2006). This toxin is widely distributed among bacterial pathogens, causing DNA damage that results in cell cycle arrest, cellular distension, and apoptosis of a broad range of mammalian cell lineages (Lara-Tejero and Galan, 2000;Lara-Tejero and Galan, 2002;Jinadasa et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Though, according to literature, efficiency of probiotics in reducing colonization of enteric pathogenic bacteria is yet inconclusive, several groups of research have proposed that the increased production of metabolites from probiotics (e.g., CLA) might improve the overall health benefits of probiotics on host, in addition to the exclusion of enteric pathogens through colonization competition in gut ecosystem 11 , 29 – 31 , 34 , 35 . In this study, we used a CJRMKm strain containing kanamycin resistance gene which was inserted into cdt of C. jejuni chromosome as shown in a previous study demonstrating that deletion of cdt did not alter the colonization capability of C. jejuni in chicken gut 36 . The 8-day-old chicks challenged with CJRMKm showed a persistent resistance to CJRMKm colonization in their gut through the effect of probiotics.…”
Section: Discussionmentioning
confidence: 99%